Pengembangan Alat Peraga Kerangka Tulang Kardus (Kudus) dalam Pembelajaran IPAS Materi Kerangka Tubuh Manusia pada Kelas VI di MI Miftahul Huda Mlokorejo - Munawwaroh, Faridatul; Suwignyo Prayogo, Muhammad; Laily Maulana, M. Hiqmal; Datul Jannah, Siti Farit (JURNAL BIOSHELL, 2024)
Natural and Social Sciences (IPAS) lessons are one of the important components in the elementary education curriculum. In learning, there are several abstract material concepts that make it difficult for students to understand them. Therefore, innovation is needed in learning, for example by utilizing and developing alat peragaor teaching aids. The development of Kudus alat peraga(Kerangka Tulang Kartu) aims to make it easier for students to understand abstract concepts such as the function and structure of the human skeleton. With the development of this media, it is hoped that it can become an effective visual aid for IPAS learning. The type of research used is Research and Development with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data analysis is in the form of qualitative and quantitative analysis. The feasibility or validity test was obtained from the validation of two experts, namely material experts and alat peragaexperts. The results of the feasibility test obtained that the validation was 78% (Valid) and for the IPAS learning material experts, the validation value was 70% (Valid). Based on these values, alat peragaexperts stated that this Kudus alat peragawas feasible and without revision. For small-scale alat peragatesters, an average of 75% (Good) was obtained for student responses, a value of 77% (Very Good) for teacher responses. And in large-scale testing, an average value of 88% (Very Good) was obtained for students, and 80% for teacher responses. From the results above, it can be concluded that the developed product is feasible to be implemented in science learning on the human skeleton material based on good and very good validity in responses from teachers and students.